2018
DOI: 10.17977/um027v1i22018p238
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Program Penguatan Pendidikan Karakter Melalui Kegiatan Pembiasaan Dalam Peningkatan Mutu Sekolah

Abstract: The purposes of this research to describe: (1) planning, (2) implementation, (3) role of school citizen, and (4) inhibiting and supporting factors in Character Education Improvement program through habituation activities in improving school quality. This research uses qualitative approach, with case study research design at SMPN 1 Wlingi Blitar. Data collection techniques interview, observation and documentation. The analysis techniques are reduction, display and conclusion. The results of this study (1) plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 0 publications
0
7
0
14
Order By: Relevance
“…When learning face to face, the school will become a place for children to be able to grow and develop the character that is in him. According to Hamid, school (education) is one of the strategic places in the formation of character in addition to the family and community (Andriani, Arifin, & Nurabadi, 2018). In line with this opinion, it is expected that in school, students can develop their characters optimally.…”
Section: The Role Of Character Education In Learningmentioning
confidence: 99%
“…When learning face to face, the school will become a place for children to be able to grow and develop the character that is in him. According to Hamid, school (education) is one of the strategic places in the formation of character in addition to the family and community (Andriani, Arifin, & Nurabadi, 2018). In line with this opinion, it is expected that in school, students can develop their characters optimally.…”
Section: The Role Of Character Education In Learningmentioning
confidence: 99%
“…From several definitions of discipline, it can be concluded that discipline is an orderly and obedient action and behavior in accordance with the rules. In addition, Andiarini and Nurabadi (2018) stated that in order to make the habituation activity a success, all components related to schools were involved to continue to support it. However, everything that supports it can also become an obstacle if it is not maximized, such as from aspects: school residents (teachers, staff and employees), students, facilities and infrastructure and parents.…”
Section: Discussionmentioning
confidence: 99%
“…The character values contained in cultural habituation are the value of tolerance, the value of cooperation, the value of resilience, the value of the economy, and the value of cultural awareness. Andiarini et al (2018) stated that the habituation at SMPN 1 Wlingi Blitar starts from planning, implementation, school members, supervisors, and implementers" roles could improve the institution"s quality of character education. Habituation by Mandailing and Angkola tribes can foster character by involving indigenous peoples, families, and schools that are still adjusted to their local wisdom to maintain cultural preservation.…”
Section: ) Habituationmentioning
confidence: 99%